A Sociological Study of the Phenomenon of Emotional Divorce in Tehran - Salemi, Hamzeh; Kazemi Pour Sabet, Shahla; Savadian, Parvin (Applied Family Therapy Journal (AFTJ), 2024)
Objective: This study aims to explore the sociological factors, contextual conditions, structural factors, and social pressures contributing to emotional divorce in Tehran.Method: The study employs a qualitative approach using a sequential exploratory design and grounded theory strategy. A purposive sample of 21 individuals, aged 25-40, with at least a bachelor's degree in psychology, sociology, or related fields, participated in semi-structured interviews. Data were analyzed using open coding and axial coding processes to identify key structures and indices related to emotional divorce. The participants included university lecturers, teachers, housewives, and private sector employees, ensuring a diverse representation of educated individuals with relevant expertise.Findings: The results indicate that attitudes and values, social and cultural pressure, and social changes are significant causal factors in the occurrence of emotional divorce. Key phenomena identified include changes in emotional relationships, lack of emotional behavior towards the spouse, emotional void, and compulsory living. Contextual conditions such as changes in culture, values, economic conditions, and types of social interactions were influential. Structural factors identified include policies and laws, and social roles. Social pressures, including peer pressure, family opinions, and media influence, were crucial intervening factors. An educational approach was identified as an effective strategy for preventing and managing emotional divorce.Conclusion: Emotional divorce, while not always visible, significantly impacts individuals and society. Understanding its sociological aspects and underlying causes is essential for developing effective prevention and management strategies. Educational programs aimed at improving emotional relationships, communication skills, and stress management can mitigate the negative impacts. Policymakers can use these insights to formulate supportive policies and laws. Further research is needed to generalize findings and explore the impact of emotional divorce on children and other regions.